Peran Stakeholder Dalam Upaya Reintegrasi Sosial Kasus Kekerasan Pada Anak di Kota Semarang - Masyhurah; Tri Yuniningsih; Ida Hayu Dwimawanti (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2021)
Children are vulnerable to becoming victims of violence in both developing and developed countries. Various regulations were made to end violence against children. Semarang City Government seeks to protect children from violence through Regional Regulation Number 05 of 2016 and forming a child protection organization through Semarang Mayor Regulation Number 05 of 2018. Implementation of social reintegration for child victims of violence in Semarang City involves many stakeholders. This study aims to analyze the role of stakeholders and determine the inhibiting factors for the role of stakeholders. The method used is descriptive qualitative. The results of the research show that The Women Empowerment and Child Protection Regional Office play a role as a policy creator, implementor, coordinator, facilitator, and accelerator. PPT SERUNI, PPT Kecamatan, and Pos JPPA play a role as implementers, coordinators, facilitators, and accelerators. Regional Offices, Rumah Duta Revolusi Mental, hospitals, academic, and Bhabinkamtibmas play a role as facilitators and accelerators of child protection and social reintegration. The inhibiting factors for social reintegration in cases of violence against children include the community culture that discriminates against victims, limited reintegration budgets, trauma in victims that causes victims to be reluctant to return to school or return to social institutions, and regulations governing social reintegration are still weak. The recommendation conveyed is that the Office of Women's Empowerment and Child Protection conducts outreach on child protection services and educates schools and social institutions about preventing violence, the importance of recovery and reintegration for victims of violence. Increase the budget for child protection and collaborate with other stakeholders to finance the social reintegration of child victims of violence. Conduct regular counseling with the psychologist PPT SERUNI or RDRM. As well as passing new regulations that explain in detail social reintegration according to the needs of victims.